A study of intravenous iron exposure in ESRD patients on haemodialysis - Hamzah, Mohd Hazlan; Mohamad Nor, Fariz Safhan; Mat Nor, Khadijah; Seman, Mohd Ramli; MK, Ahmad; Draman, Che Rosle; Wan Ali, Wan Ahmad Syahril Rozli (John Wiley & Sons, Inc., 2015)
Introduction Intravenous iron in combination with erythropoietin therapy is essential in maintaining optimal haemoglobin level. However, data is limited on whether over exposure of iron is associated with increased morbidity and mortality in ESRD patients on haemodialysis (HD), especially infection related. Objectives To evaluate any association between cumulative iron dose and episodes of infections, all cause hospitalizations and mortality in patients on HD. Method All newly diagnosed ESRD patients initiated on HD in Pahang State of Malaysia government dialysis centers between 1 January 2014 and 31 December 2014 were included. Baseline demographics, cumulative iron dose (IV Cosmofer) over 3 months, haemoglobin level, ferritin level and transferrin saturation ratios (TSAT) were recorded. Patients’ outcome of infections, all causes hospitalisations and mortality were analysed. Results